1998
DOI: 10.1152/ajpheart.1998.275.2.h600
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporal injection ofhSlocDNA in rats produces physiologically relevant alterations in penile function

Abstract: The Ca2+-sensitive K+ channel (maxi-K+) is an important modulator of corporal smooth muscle tone. The goal of these studies was twofold: 1) to determine the feasibility of transfecting corporal smooth muscle cells in vivo with the hSlo cDNA, which encodes for the human smooth muscle maxi-K+channel, and 2) to determine whether transfection of the maxi-K+channel would affect the physiological response to cavernous nerve stimulation in a rat model in vivo. Intracorporal microinjection of pCMVβ/Lac Z DNA in 10-wk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 26 publications
0
134
0
3
Order By: Relevance
“…These results support the hypothesis that in vivo gene transfer of NOS isoforms and K channel openers can augment the erectile response to nerve stimulation in the aged rat. 14,16 It is reasonable to assume that NOS will become an important target gene for gene therapy strategy because of its vital pharmacological role in the process of penile erection. These data suggest that adenoviral mediated transfer of the eNOS gene or other NOS isoforms may represent an exciting new form of therapy for the treatment of male erectile dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support the hypothesis that in vivo gene transfer of NOS isoforms and K channel openers can augment the erectile response to nerve stimulation in the aged rat. 14,16 It is reasonable to assume that NOS will become an important target gene for gene therapy strategy because of its vital pharmacological role in the process of penile erection. These data suggest that adenoviral mediated transfer of the eNOS gene or other NOS isoforms may represent an exciting new form of therapy for the treatment of male erectile dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…14, 15 Christ and colleagues reported that injecting cDNA encoding hSlo, a maxi-K channel, increased gap junction formation and enhanced erectile responses to nerve stimulation in aged rats. 14 Garban and colleagues injected cDNA encoding RPiNOS into the corpus cavernosum of the aged rat and reversed age-related erectile dysfunction. 16 This study provided evidence that in vivo gene transfer of NOS isoforms can have physiologically bene®cial consequences on failing erections in aged rats.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological approaches targeting smooth muscle cells and neuronal tissue are most relevant (55,56) (59,60). Pathophysiology.…”
Section: Male Sexual Dysfunctionmentioning
confidence: 99%
“…Thus, with respect to ED, despite the more limited smooth muscle expression profile, the CN-stimulated ICP response for pSMAA-hSlo compares quite favorably to that observed with hSlo expression driven by the heterologously expressed CMV promoter (the vector used in the recently completed Phase I human clinical trial), [17][18][19][20] as well as our prior preclinical observations with pcDNA/hSlo. [14][15][16] Again, it is important to keep in mind that gene transfer with both promoters produces an ICP/BP ratio commensurate with an erection; that is, an ICP/BP ratio of more than 0.6. As discussed elsewhere, the probability of visualizing an erection during CN stimulation increases dramatically as the ICP/BP ratio becomes 0.6 or more.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] These studies were performed with a naked DNA vector, pcDNA-hSlo, in which Slo gene expression is driven by the cytomegalovirus (CMV) promoter, which functions in the majority of both human and animal tissues. A bacterial selectable marker (the penicillin-resistance gene, ampR) is present in this plasmid.…”
Section: Introductionmentioning
confidence: 99%